PENYULUHAN HUKUM: PENGABDIAN KEPADA MASYARAKAT DALAM KESADARAN HUKUM SISWA SMA PASUNDAN 1 BANDUNG TENTANG AKIBAT HUKUM BULLYING - Haswar Widjanarto; Agam Prawira (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT Bullying in the school environment is a social issue that can have negative impacts on students' psychological well-being, academic performance, and character development. The limited understanding among students regarding the forms, impacts, and legal consequences of bullying served as the basis for implementing a legal education program for senior high school students. This activity aimed to enhance students' legal awareness and understanding of bullying prevention, as well as the legal consequences that may be imposed on perpetrators under Indonesian laws and regulations. The study employed an empirical legal approach with a qualitative descriptive design, consisting of three stages: preparation, implementation, and evaluation. The educational materials were delivered using participatory methods, including interactive lectures, group discussions, case studies, and role-playing activities. The program was evaluated through observations and questionnaires administered to 10 participants. The results indicated that the legal education program improved students' understanding of the impacts of bullying, the importance of prevention, and the responsibility of every individual in creating a safe school environment. Based on the evaluation questionnaire, nine participants reported that they understood the materials presented, while one participant reported having a sufficient level of understanding. In addition, nine participants demonstrated an understanding of the procedures for reporting bullying incidents to the school authorities and expressed their willingness to report bullying if they witnessed or experienced such incidents. Nevertheless, three participants still expressed concerns about the possibility of bullying occurring within the school environment. Overall, the evaluation findings indicate that the legal education program was effective in improving students' legal awareness and understanding and can serve as an educational strategy to support the development of a safe, inclusive, and bullying-free school culture. ABSTRAK Bullying di lingkungan sekolah merupakan permasalahan sosial yang dapat memberikan dampak negatif terhadap kondisi psikologis, prestasi belajar, dan perkembangan karakter siswa. Rendahnya pemahaman siswa mengenai bentuk, dampak, serta konsekuensi hukum tindakan bullying menjadi dasar pelaksanaan kegiatan penyuluhan hukum kepada siswa Sekolah Menengah Atas (SMA). Kegiatan ini bertujuan untuk meningkatkan pemahaman dan kesadaran hukum siswa mengenai pencegahan bullying serta akibat hukum yang dapat diterapkan terhadap pelaku berdasarkan peraturan perundang-undangan di Indonesia. Metode yang digunakan adalah pendekatan hukum empiris dengan desain deskriptif kualitatif melalui tiga tahapan kegiatan, yaitu persiapan, pelaksanaan, dan evaluasi. Penyampaian materi dilakukan secara partisipatif melalui ceramah interaktif, diskusi kelompok, studi kasus, dan role play. Evaluasi kegiatan dilakukan melalui observasi dan kuesioner terhadap 10 peserta. Hasil kegiatan menunjukkan bahwa penyuluhan hukum mampu meningkatkan pemahaman siswa mengenai dampak bullying, pentingnya pencegahan, serta tanggung jawab setiap individu dalam menciptakan lingkungan sekolah yang aman. Berdasarkan hasil kuesioner evaluasi terhadap 10 peserta, sebanyak 9 peserta menyatakan telah memahami materi yang disampaikan, sedangkan 1 peserta menyatakan cukup memahami. Selain itu, 9 peserta memahami mekanisme pelaporan tindakan bullying kepada pihak sekolah dan menyatakan bersedia melaporkan apabila mengetahui atau mengalami tindakan bullying. Meskipun demikian, 3 peserta masih menyampaikan kekhawatiran terhadap kemungkinan terjadinya bullying di lingkungan sekolah. Hasil evaluasi tersebut menunjukkan bahwa penyuluhan hukum efektif meningkatkan pemahaman dan kesadaran hukum siswa serta dapat menjadi strategi edukatif dalam mendukung terciptanya budaya sekolah yang aman, inklusif, dan bebas dari bullying.